Negotiating Love and Faith: Interfaith Marriage in Manado, Indonesia - Rosdalina Bukido; Edi Gunawan; Djamila Usup; Hayat Hayat (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
Interfaith marriages in people's lives have been practised in many areas in Indonesia, even if it's not legally registered. The rule of law in Indonesia does not accommodate interfaith marriages. When interfaith marriage happens, the registration system should follow marriage registration either at the KUA (office of religious affairs) for Muslims or in the Civil Registry office for other religions. This study aims to analyse the practice of interreligious marriage in Manado and how they maintain a good marital relationship between the spouse of different religions. This research employs a qualitative approach by collecting data through interviews with 30 informants who practice interfaith marriages in Manado. The results of this research found that many people in Manado consider interfaith marriage as permissible. They argue that religion is a relationship between humans and God, while marriage is related to human beings. The family of different religions based their relationship on the principle of "Torang Samua Basudara" (we are bound through kinship). Based on this principle, the family avoids using religious symbols in their communication that can cause tension and disrupt harmony among family members. The principle of torang samua basudara is the basis for establishing good communication in the family.